Pelatihan Penerapan Kurikulum Merdeka Kelompok Kerja Guru-Guru Tingkat Sekolah Dasar Se-Kecamatan Kuok - Mukhlis, Muhammad; Yuliawan, Tri; Alber, Alber; Shomary, Sudirman; Erni, Erni; Asnawi, Asnawi; Asnidar, Asnidar; Sutarsa, I Ketut; Priyadi, Priyadi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Training on Implementing the Independent Curriculum for working groups of elementary school teachers throughout Kuok District aims to increase teacher competency and readiness in implementing this new curriculum. This training was carried out using offline and online methods, involving 26 participants from various elementary schools. Implementation of activities includes preparation, implementation and evaluation stages, with the core activities being the delivery of interactive material, simulation practice and final evaluation. The results of the training showed a significant increase in teachers' understanding and skills regarding the Independent Curriculum. Teachers are able to develop innovative teaching modules and design effective learning processes. Positive evaluations and feedback from participants confirm the success of this training. To overcome obstacles, several solutions and innovations were proposed, including the use of information technology and regular assistance. It is hoped that this training can contribute to improving the quality of education in Kuok District, support the sustainable implementation of the Independent Curriculum, and create a young generation that is competent in facing global challenges.